EU project "Cheap-GSHPs": the geoexchange field laboratory. (September 2017) - Galgaro, Antonio; Santa, Giorgia Dalla; Cultrera, Matteo; Bertermann, David; Mueller, Johannes; De Carli, Michele; Emmi, Giuseppe; Zarrella, Angelo; Di Tuccio, Maria; Pockelé, Luc; Mezzasalma, Giulia; Psyk, Mario; et al.
Abstract: The Molinella test site is the open-air laboratory of the EU project entitled "Cheap-GSHPs: Cheap and Efficient Application of Reliable Ground Source Heat Exchangers and Pumps". Here, innovative helical heat baskets and steel coaxial probes are installed next to the traditional double-U. The tests involve the probes design as well as materials and drilling techniques and machines, therefore the newly developed GSHEs can be directly compared with the traditional ones with respect to technical issues and energetic performances. The Molinella test site therefore represents a very extraordinary possibility to improve the knowledge of heat transfer processes in shallow geo-exchange systems.